Trends and prospects in solution-cast polymer electrolytes: From processing simplicity to performance complexity - Adam, Abdullahi Abbas; Zainol, Norazwina; Manfo, Theodore Azemtsop; Karim, Mohamad Shaiful Abdul (Elsevier, 2026)
Solution casting, once valued for its simplicity as a film-forming technique, has now matured into a versatile and powerful route for designing advanced solid and gel polymer electrolytes. Its low cost, reproducibility, and adaptability uniquely position it to bridge fundamental materials science with practical device integration. In recent years, solution-cast polymer electrolytes have evolved beyond processing simplicity to becoming engineered platforms where ion transport pathways, structural architectures, and additive chemistries are tailored. This evolution addresses intrinsic limitations such as low room-temperature conductivity, poor interfacial contact, and fragile mechanical strength. Advances stem from approaches that control polymer crystallinity, strengthen polymer-ion interactions, and use of electrolyte additives (such as plasticizers, fillers, MXenes, metal organic frameworks and deep eutectic solvents) to elevate ionic conductivity, widen electrochemical stability windows and promote mechanical robustness. At the same time, the incorporation of bio-based and recyclable polymers has extended these advances into the realm of sustainability, aligning electrolyte innovation with environmental responsibility. Together, these developments demonstrate how a simple processing method has given rise to performance complexity, enabling polymer electrolytes to compete with their liquid and inorganic counterparts. This review critically evaluates these advances, tracing how processing innovations translate into functional performance. It also highlights the trends and prospects most likely to shape the development of frontier solid-state batteries and supercapacitors.
Keywords: Polymer electrolytes; Solution casting; Natural biopolymers; Synthetic polymers; Supercapacitors; Batteries; fi=Sähkötekniikka|en=Electrical Engineering|